2014
DOI: 10.3109/14992027.2014.986691
|View full text |Cite
|
Sign up to set email alerts
|

College students’ personal listening device usage and knowledge

Abstract: Despite reported knowledge of hearing loss risk due to PLD use in virtually all college students, 1 in 4 were found to listen to their PLDs at free-field equivalent levels greater than 80-dBA, with 94% unaware of their potential risk. Further research is needed to provide accurate PLD listening information and evaluate the possibility of long term PLD intensities that surpass recommended safety levels on hearing loss in adults over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The overall effect size of the DPOAEs was 0.089 (CI −0.012 to 0.190; p 0.080, I 2 0%), indicating no significant amplitude change within 24 h after music exposure. In sum, the short-term result after music exposure did not show any meaningful changes for PTA thresholds or DPOAE amplitudes To identify the long-term hearing changes after music exposure [9,21,22,24,26,30,31,33,34], the pooled studies for analysis are shown in Figures 4 and 5 for PTA and DPOAE, respectively, in the same frequencies along with the short-term hearing changes. Similar to PTA outputs, the amplitude of DPOAEs showed the largest effect size also at 4 kHz (0.124, CI −0.047 to 0.296; p 0.155) (see Figure 3).…”
Section: Meta-analysis Of Music Exposure Effects With Subgroup Analysismentioning
confidence: 99%
“…The authors confirmed that four [9,[20][21][22] of the selected studies had "good" quality (scored 7-9). The remaining studies were evaluated as having "fair" quality (score 4-6) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] except for one study with a score of 3, evaluated as having "poor" quality [35]. Thus, 16 articles were included for systematic review and meta-analysis in this study.…”
Section: Selection Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…students, in particular, were found to listen to music with PlDs in excess of safe listening levels and durations that posed a risk of hearing loss. on the other hand, regarding the health belief model, it is expected that medical students engage in behaviors to reduce danger and rather enhance protective behaviors connected with listening to music [7,8].…”
Section: Introductionmentioning
confidence: 99%